2023
DOI: 10.1002/anie.202214208
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Charge Transport in a 2D/3D Perovskite Heterostructure by Selecting an Ordered 2D Perovskite as the Passivator

Abstract: We demonstrate that an ordered 2D perovskite can significantly boost the photoelectric performance of 2D/3D perovskite heterostructures. Using selective fluorination of phenyl-ethyl ammonium (PEA) lead iodide to passivate 3D FA 0.8 Cs 0.2 PbI 3 , we find that the 2D/3D perovskite heterostructures passivated by a higher ordered 2D perovskite have lower Urbach energy, yielding a remarkable increase in photoluminescence (PL) intensity, PL lifetime, charge-carrier mobilities (ϕμ), and carrier diffusion length (L D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Thiocyanate-based perovskites are constructed by Pb-centered octahedra with two axial thiocyanate anions and four equatorial halide anions. The A-site cations are sandwiched between the layers, providing charge balance. The SCN – anions inserted into the inorganic lattices can act as a probe to reflect the orientation of inorganic lattices. , SFG-VS is a second-order coherent nonlinear optical technique that is powerful for determining the structure, dynamics, and interaction of molecules in symmetry-broken environments. , It has been applied to probe the orientation and structural ordering of organic cations in 2D OIHPs. Our results indicated that the orientation angle of SCN – anions has a strong correlation with the electron–phonon interaction and effective charge-carrier mobility. A more parallel orientation of SCN – anions leads to a higher electron–phonon interaction and lower effective charge-carrier mobility.…”
Section: Introductionmentioning
confidence: 87%
“…Thiocyanate-based perovskites are constructed by Pb-centered octahedra with two axial thiocyanate anions and four equatorial halide anions. The A-site cations are sandwiched between the layers, providing charge balance. The SCN – anions inserted into the inorganic lattices can act as a probe to reflect the orientation of inorganic lattices. , SFG-VS is a second-order coherent nonlinear optical technique that is powerful for determining the structure, dynamics, and interaction of molecules in symmetry-broken environments. , It has been applied to probe the orientation and structural ordering of organic cations in 2D OIHPs. Our results indicated that the orientation angle of SCN – anions has a strong correlation with the electron–phonon interaction and effective charge-carrier mobility. A more parallel orientation of SCN – anions leads to a higher electron–phonon interaction and lower effective charge-carrier mobility.…”
Section: Introductionmentioning
confidence: 87%
“…[1][2][3][4][5][6][7][8][9] This amazing development of PSCs is mainly due to the appealing photoelectric characteristics of perovskite materials, such as long carrier diffusion length, superior light harvesting capability, low defect state density and tunable bandgaps. [10][11][12][13][14] Furthermore, the advantages of PSCs such as simple-preparation processing, low-cost materials, and highefficient performance also give perovskite materials great potential for commercial application. 15,16 However, there still exist lots of challenges on the road to commercialization of PSCs, 17,18 such as grain boundary and interface defects, [19][20][21] which can lead to severe trap-assisted Shockley-Read-Hall (SRH) complexation, [22][23][24] poor long-term operation stability due to heat-, water-, and light-induced degradation, hysteresis and phase separation problems dictated by the incidental ion migration.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the structural ordering is estimated by the effective molecular number (⟨ N ⟩) contributing to the SFG signals. A relative structural ordering (RSO) with ⟨ N pH2 ⟩ as the reference is then defined as eq due to the close Fresnel factors at different pH values where ⟨ N pH ⟩ is given by eq , where β lmn (l, m, n = a, b, c) is the molecular hyperpolarizability in the molecular (a, b, c) coordinate system.…”
mentioning
confidence: 99%
“…A relative structural ordering (RSO) with ⟨ N pH2 ⟩ as the reference is then defined as eq due to the close Fresnel factors at different pH values where ⟨ N pH ⟩ is given by eq , where β lmn (l, m, n = a, b, c) is the molecular hyperpolarizability in the molecular (a, b, c) coordinate system. θ is the tilt angle of the −SO 3 – group (Figure S3).…”
mentioning
confidence: 99%
See 1 more Smart Citation